Design and psychometric validation of a metacognitive instrument for physics learning: A focus on heat concepts - Hera Novia; Siska Dewi Aryani; Andhy Setiawan; Muhammad Zahran (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Metacognitive knowledge, awareness of one's own cognition, tasks, and learning strategies, is critical for independent learning but is often underemphasized in physics education. Aim: This study aimed to develop and validate a questionnaire to measure high school students’ metacognitive knowledge within the specific context of physics, focusing on the topic of heat. Method: The research involved content validation by six physics education experts and construct validation through empirical testing with 163 high school students. Content validity was established using Aiken’s V, while construct validity and reliability were evaluated using Rasch model analysis. Results: The final instrument consisted of 28 items, of which 26 met the Rasch model fit criteria. The analysis confirmed high person reliability (0.82) and item reliability (0.98), indicating strong internal consistency and measurement stability. Conclusion: The findings support the questionnaire's validity and reliability as a tool for assessing metacognitive knowledge in physics. This validated instrument provides a foundation for future research and instructional practices aimed at enhancing students' metacognitive skills